The Role of Tax Judiciary in Reducing Tax Evasion - Qasem Kadem Hamed (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
In this study, we explore how the tax judiciary can reduce tax evasion and promote compliance in different legal and economic environments. Utilizing qualitative and quantitative analysis in a mixed-methods effort, the article explores the varied judicial contexts, resolutions, and the implications on how taxpayers behave. These findings underscore the important role that judicial interventions play in raising compliance rates, with comparative lessons from Iraq, Germany, and the United States. Although efficient mechanisms for judiciary review exhibit a strong link to improved compliance, low public awareness, resource constraints, and procedural delays have affected optimal performance in the Global South. Key Takeaway: The study emphasizes the need for enhancing technology integration and improving coordination between judicial systems and tax authorities to enable fair enforcement and efficient resolution of disputes. They enhance the literature on tax governance by providing empirical recommendations for increasing judicial efficiency and fundamentals in light of contemporary challenges associated with globalization and digitalization. Potential areas of future research include the use of advanced technologies in changing tax judiciary practices, such as artificial intelligence (AI) and blockchain.